Historical dictionary of science fiction cinema - Booker, Marvin Keith 1953- (Historical dictionaries of literature and the arts, 2020)
"This second edition of Historical Dictionary of Science Fiction Cinema contains a chronology, an introduction, and an extensive bibliography. The dictionary section has over 400 cross-referenced entries on important personalities, films, companies, techniques, themes, and sub genres"--